British elite swimmers’ experiences and perspectives on life skill development - Murdoch, Ross; Hong, Hee Jung (Frontiers in Psychology, 2024)
This study explores the experiences of British elite swimmers in developing life skills during and throughout their athletic careers, examining the factors that influence their perspectives on this skill development. Six high-profile British swimmers, who have competed at the Commonwealth and/or Olympic Games, were recruited for this study. Semi-structured interviews were conducted, and thematic analysis was applied. Through the analysis, two key themes were identified from the thematic analysis: (a) Implicit life skill development through athletic and educational experience, and (b) Understanding the influence of swimming on life skill development. The first theme includes three sub-themes: (a) Establishment of athletic identity, (b) Prioritization of athletic identity, and (c) Navigating life skills through athletic challenges. The findings show that the swimming careers of participants and their associated identities contributed to the development of a wide range of implicit life skills. This growth was facilitated by both educational and sporting experiences, with all participants reporting positive personal development from their time in competitive swimming. The findings in this study enhance our understanding of life skill development and provide insights into how to more effectively support high-performance athletes in both their athletic careers and educational endeavors.